M-learning curriculum design for secondary school: A needs analysis - Shuib, A.S.; Siraj, Saedah; Abdullah, M.R.T.L. (2010)
The learning society has currently transformed from ‘wired society’ to become ‘mobile society’ which is facilitated by wireless network. To suit to this new paradigm, mlearning was given birth and rapidly building its prospect to be included in the future curriculum. Research and studies on mlearning spruced up in numerous aspects but there is still scarcity in studies on curriculum design of m-learning. This study is a part of an ongoing bigger study probing into the m-learning curriculum for secondary schools. The paper reports on the first phase of the study which aims to probe into the needs of curriculum design for m-learning at the secondary school level and the researchers adopted the needs analysis method. Data accrued from responses on survey questionnaires based on Lickert-point scale were analyzed statistically. The findings from this preliminary study serve as a basis for m-learning curriculum development for secondary schools